Relationship between tennis serve velocity and select performance measures - Hayes, M. J.; Spits, D. R.; Watts, D. G.; Kelly, V. G. (The Journal of Strength and Conditioning Research, 2021)
The purpose of this study was to determine whether there was a relationship between tennis serve speed and isometric midthigh pull (IMTP) kinetic variables: countermovement jump (CMJ) height, shoulder internal and external rotation strength, and anthropometric measures in elite adolescent tennis players. Twenty-one elite junior tennis players from the Tennis Australia National Academy were recruited for this study (male, n = 12 and female, n = 9). Correlations between the performance variables and peak tennis serve speed were calculated using a Pearson's product-moment correlation coefficient. A significant positive correlation was found between peak serve speed and body height (r = 0.80, p < 0.01), IMTP peak force (r = 0.87, p < 0.01), CMJ height (r = 0.77, p = 0.01), and impulse at 300 ms (r = 0.71, p = 0.01). A significant, strong correlation was found between peak serve speed and impulse at 100 ms (r = 0.58, p = 0.01), impulse at 200 ms (r = 0.64, p = 0.01), internal rotation <90° (r = 0.63, p = 0.01), and external rotation <90° (r = 0.63, p = 0.01). Because of the significant positive correlations between IMTP variables, CMJ height and peak serve speed, strength and conditioning coaches with access to a force plate should consider using the IMTP to athletically profile athletes in regards to their strength, power, and injury risk.